The Adenovirus E4-ORF3 Protein Stimulates SUMOylation of General Transcription Factor TFII-I to Direct Proteasomal Degradation - Rebecca G. Bridges (American Society for Microbiology, 2016)
ABSTRACT Modulation of host cell transcription, translation, and posttranslational modification processes is critical for the ability of many viruses to replicate efficiently within host cells. The human adenovirus (Ad) early region 4 open reading frame 3 (E4-ORF3) protein forms unique inclusions throughout the nuclei of infected cells and inhibits the antiviral Mre11-Rad50-Nbs1 DNA repair complex through relocalization. E4-ORF3 also induces SUMOylation of Mre11 and Nbs1. We recently identified additional cellular targets of E4-ORF3 and found that E4-ORF3 stimulates ubiquitin-like modification of 41 cellular proteins involved in a wide variety of processes. Among the proteins most abundantly modified in an E4-ORF3-dependent manner was the general transcription factor II–I (TFII-I). Analysis of Ad-infected cells revealed that E4-ORF3 induces TFII-I relocalization and SUMOylation early during infection. In the present study, we explored the relationship between E4-ORF3 and TFII-I. We found that Ad infection or ectopic E4-ORF3 expression leads to SUMOylation of TFII-I that precedes a rapid decline in TFII-I protein levels. We also show that E4-ORF3 is required for ubiquitination of TFII-I and subsequent proteasomal degradation. This is the first evidence that E4-ORF3 regulates ubiquitination. Interestingly, we found that E4-ORF3 modulation of TFII-I occurs in diverse cell types but only E4-ORF3 of Ad species C regulates TFII-I, providing critical insight into the mechanism by which E4-ORF3 targets TFII-I. Finally, we show that E4-ORF3 stimulates the activity of a TFII-I-repressed viral promoter during infection. Our results characterize a novel mechanism of TFII-I regulation by Ad and highlight how a viral protein can modulate a critical cellular transcription factor during infection. IMPORTANCE Adenovirus has evolved a number of mechanisms to target host signaling pathways in order to optimize the cellular environment during infection. E4-ORF3 is a small viral protein made early during infection, and it is critical for inactivating host antiviral responses. In addition to its ability to capture and reorganize cellular proteins, E4-ORF3 also regulates posttranslational modifications of target proteins, but little is known about the functional consequences of these modifications. We recently identified TFII-I as a novel target of E4-ORF3 that is relocalized into dynamic E4-ORF3 nuclear structures and subjected to E4-ORF3-mediated SUMO modification. Here, we show that TFII-I is targeted by E4-ORF3 for ubiquitination and proteasomal degradation and that E4-ORF3 stimulates gene expression from a TFII-I-repressed viral promoter. Our findings suggest that the specific targeting of TFII-I by E4-ORF3 is a mechanism to inactivate its antiviral properties. These studies provide further insight into how E4-ORF3 functions to counteract host antiviral responses.